Towards storage-stable high-content recycled tyre rubber modified bitumen - Lo Presti, D.; Izquierdo, M.A.; Jiménez del Barco Carrión, A. (Elsevier, 2018)
The addition of crumb rubber particles as bitumen modifier can be currently considered as a well-established alternative to conventional polymers for bitumen modification. However, Recycle Tyre Rubber (RTR) modified binders still present drawbacks such as poor mix workability and hot storage stability. Within this study the authors try unlocking the full potential of devulcanised tyre rubber-heavy oils blend, named Liquid Rubber (LR), by exploring the possibility of tailoring recycled polymer modified bitumen with unconventional high-content of RTR and designed to overcome the above mentioned technological problems of RTR modified bitumen while keeping its advantages. Results show that LR-bitumen blends incorporating up to 30% RTR in weight of total binder clearly improves useful temperature interval of base bitumen by maintaining solubility values allowing them to be considered stable at hot-storage temperature. Furthermore, the LR modifier allows reducing usual manufacture temperatures up to 30 °C by providing superior low and intermediate temperature rheology, however high service temperature properties are improved only at low strain.